2017
DOI: 10.1108/jiabr-10-2015-0052
|View full text |Cite
|
Sign up to set email alerts
|

Shariah-compliant investments and stock returns: evidence from the Indonesian stock market

Abstract: Purpose The purpose of this paper is to investigate the impact of the Indonesia Shariah-compliant Stock Index (ISSI) on the performance of included shares. In essence, the authors ask whether the establishment of the ISSI provides abnormal returns for the firms that are not included in the Jakarta Index. Design/methodology/approach The authors use an event study methodology to estimate cumulative abnormal returns in the days surrounding the event to examine the relationship between Shariah-compliant investme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 40 publications
0
26
0
1
Order By: Relevance
“…Kumar & Sahu (2017), found the presence of a long run equilibrium relation between macroeconomic indicators and Dow Jones Islamic India market index. On the other hand, Lusyana & Sherif (2017) found that the inclusion of the ISSI has a positive impact on the financial performance of the included shares during the 41-day event window. Furthemore, El Ouadghiri & Peillex (2018), found that US public attention to Islamic terrorism negatively affects US Islamic indices, suggesting that investors may make amalgams between terrorism and Islamic finance.…”
Section: Introductionmentioning
confidence: 90%
“…Kumar & Sahu (2017), found the presence of a long run equilibrium relation between macroeconomic indicators and Dow Jones Islamic India market index. On the other hand, Lusyana & Sherif (2017) found that the inclusion of the ISSI has a positive impact on the financial performance of the included shares during the 41-day event window. Furthemore, El Ouadghiri & Peillex (2018), found that US public attention to Islamic terrorism negatively affects US Islamic indices, suggesting that investors may make amalgams between terrorism and Islamic finance.…”
Section: Introductionmentioning
confidence: 90%
“…Islamic and ethical finance have a similar objective, in that individuals allocate their funds in a manner consistent with their morals and faith (Bennett & Iqbal, 2013). More specifically, morals in Islamic finance emphasise investing activity that complies with sharia principles (Lusyana & Sherif, 2017). There are many investment instruments in the Islamic capital market, including Islamic stocks, sukuk, and Islamic mutual funds.…”
Section: Islamic Equity Screening and Developmentmentioning
confidence: 99%
“…Majdoub et al (2016) suggest that Indonesian Islamic stocks offer international diversification due to their low comovement with the stock market in developed countries. Moreover, in terms of the risk-return profile, Islamic portfolios have low systematic risk and outperform their non-Islamic counterparts (Lusyana & Sherif, 2017;Qoyum et al, 2020).…”
Section: Financial Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…The Jakarta Islamic Index gives information to investors about Islamic shares (Pranata & Nurzanah, 2015). Moreover, Lusyana and Sherif (2017) suggested that Islamic capital markets had rapidly grown since the world financial crisis in 2008. In addition, they agreed that the attractiveness of the Islamic capital market in Indonesia could be seen that there were positive abnormal returns in Sharia stocks.…”
Section: Introductionmentioning
confidence: 99%